Observations sur les ecrits modernes. - Desfontaines, Pierre-François Guyot, 1685-1745. (Paris, Chaubert., 1735)
4-year index included in every fourth volume.
By Desfontaines, Granet, A.M. de Mairault and others.
Mode of access: Internet.
committed to retain
Keywords: Books -- Reviews; French periodicals; Reviews